Work performed for the Course "The Reader and their information needs" - Chacón Rojas, Gilda (1982)
This work compiles all the information brings over of: Types of users, orientation and education, evaluation of the services, equipment and materials which possesses the Bilblioteca Sor Onorina Leporati of the College Maria Auxiliadora de Alajuela.